FAKTOR LITERASI, FAKTOR PENGETAHUAN DAN FAKTOR KEPERCAYAAN DALAM MENJELASKAN INTENSIONAL TRANSAKSI PASAR MODAL DI INDONESIA (STUDI KASUS MAHASISWA STIE-IBEK PANGKALPINANG) - Misael, Hizkia; Panjaitan, Fery; Mulyani, Hendarti Tri Setyo (Jurnal Progresif Manajemen Bisnis, 2023)
Analysis of Literacy Factors, Knowledge and Trust in Explaining Intentional Capital Market Transactions in Indonesia (Case Study of STIE-IBEK Pangkalpinang Students). This study aims to analyze the influence of Literacy Factors, Knowledge, and Trust on Intentional Capital Markets in Indonesia (Case Study of STIE IBEK Pangkalpinang Students) both partially and simultaneously. The number of samples used in this study were 60 respondents. The type of data is primary dataobtained by distributing questionnaires to respondents. The data analysis method used ismultiple linear regression analysis. The results of testing the hypothesis in this study indicate that simultaneously the Literacy Factor, the Knowledge Factor, and the Trust Factor have a significant effect on Intentional Investment with a calculated f value (53.972) > f table (2.76). Partially, the Literacy Factor influences the Capital Market Intentions in Indonesia with a t- count (0.323) greater than t-table (0.2997). While the Knowledge Factor has an effect on the Capital Market Intentions in Indonesia with a t-count value (2.512) greater than t-table (0.2997), and the Trust Factor has aneffect on Capital Market Intentions in Indonesia with a t-count value (3.870) greater than t -table(0.2997).